Warfarin versus Dabigatran: the Superior Option - El Balaa, Aya; Castonguay, Krista (Université d'Ottawa | University of Ottawa, 2016)
Background: Atrial fibrillation (AF) is an arrhythmia that increases the risks of blood clots, stroke, heart failure. Oral antithrombotic and anticoagulation have been associated with the reduced formation of thrombus thus reducing the risk of AF-related stroke. Novel oral anticoagulants (NOACs) were developed in response to the downfalls of Warfarin. The first of which was dabigatran, an oral prodrug, and thrombin inhibitor. Objectives: The purpose of this study is to review the literature comparing warfarin and dabigatran on their efficacy (rates of stoke and systemic embolism), cost-effectiveness, and safety (events of major hemorrhage). Cost-effectiveness was determined based on quality adjusted life-years (QALYs). Methodology: Medline (Ovid) was used as a database with the search terms: stroke, warfarin, dabigatran, and AF. Limited to English, full text, published from 1999-2016 six articles were then reviewed for their use in this abstract. Two fundamental studies were not revealed by the original search, but was sourced by all articles chosen and was therefore included. Eight articles were used. Results: Dabigatran is prescribed in a 110 mg dose (D110) or a 150 mg dose (D150) twice daily. It was found that D110 had similar efficacy to warfarin but improved safety rates. D150 had decreased rates of stroke and systemic embolism compared to warfarin, but similar rates of major hemorrhage. In addition, Dabigatran safety may differ between sexes, Thirdly, NOACs are more expensive but more cost-effective than warfarin based on QALYs. D150 cost less than D110 per improvement in QALYs. Conclusion: Both doses of dabigatran were found to be non-inferior to warfarin for safety and efficacy rates. D150 was superior in regards to efficacy rates. D110 was superior in regards to safety. D150 was superior to D110 and warfarin in cost-effectiveness. Future exploration into a tailored dose of Dabigatran and sex-differences will prove beneficial.